SWATH-MS based quantitative proteomics analysis to evaluate the antileishmanial effect of Commiphora wightii- Guggul and amphotericin B on a clinical isolate of Leishmania donovani (vol 223, 103800, 2020) - Routaray, Chinmayee Bar; Bhor, Renuka; Bai, Shakuntala; Kadam, Nitin Suryakant; Jagtap, Surabhi; Doshi, Pooja Jignesh; Sundar, Shyam; Sawant, Sangeeta; Kulkarni, Mahesh J.; Pai, Kalpana (Journal of Proteomics, 2021)
Drug resistance and relapse after treatment of visceral leishmaniasis (VL) with the chemotherapeutic drugs has impeded the VL elimination programme especially, in the endemic region of Bihar, India. Currently, Antimonials (Sbv) have been rendered obsolete (Bihar) as frequent treatment failure and relapse in Sbv treated patient's warrants greater vigilance and attention to the limited drugs. A clinical isolate of L.donovani obtained from an Amphotericin B (AmB) relapse patient was evaluated for its susceptibility to AmB and a hyperlipidemic drug Guggul. The evaluation of susceptibility or resistance to any drug still relies on in vitro assay on promastigote and amastigote stages of Leishmania spp. as there are no validated markers which can ascertain drug resistance in Leishmania. The anti-promastigote effect of AmB and Guggul were demonstrated by significant cellular and morphological changes exhibiting apoptosis-mediated cell death. To further illustrate the molecular mechanism of the parasite's response upon exposure to either AmB and Guggul, sequential window acquisition of all theoretical fragment ion spectra mass spectrometry (SWATH-MS) for quantitative proteomics analysis was performed along with computational data analysis; revealing considerable differences in the proteome profiles which could be regarded as putative markers for resistance or drug targets for development of therapeutic antileishmanials.